Evidence of Big-Five personality changes following acquired brain injury from a prospective longitudinal investigation - Schmukle, Stefan C.; Exner, Cornelia; Leonhardt, Anne (My University, 2016)
Objective: Many studies using different assessment methods have reported personality changes after acquired brain injury (ABI). However, to our knowledge, no prospective study has yet been conducted to examine whether previous cross-sectional and retrospective results can be replicated in a longitudinal prospective design. Further, because clinical control groups were only rarely used, it remains debatable if the personality changes found are unique to patients with ABI or if they also affect patients with other disabilities. Methods: This study examined personality change in 114 participants with different kinds of ABI, 1321 matched controls (general control, GC), and 746 matched participants with restrictive impairments other than brain injury (clinical control, CC) in a prospective longitudinal design using data from the panel survey Household, Income and Labour Dynamics in Australia (HILDA). Results: Participants with ABI showed significantly larger declines in Extraversion and Conscientiousness compared with the GC group. When the ABI participants were compared with the CC group, only the difference in Conscientiousness remained significant. Conclusion: Our prospective data corroborate evidence from previous cross-sectional studies that patients with ABI experience larger declines in Extraversion and Conscientiousness than the general population. Whereas the effect on Conscientiousness was unique to patients with ABI, the decline in Extraversion was also observed in participants with other impairments.
Keywords: Health -- Mental; Surveys and Survey Methodology; Beliefs and Values -- Personality; Surveys and Survey Methodology; Health and wellbeing; Surveys and survey methodology; Beliefs and Values; Surveys and Survey Methodology; Health; Personality; Mental; Health and wellbeing; Surveys and Survey Methodology